Yemen Policy Note 1 : A Summary - World Bank Group (World Bank, Washington, DC, 2017)
Yemen is subjected to a deepening conflict with an uncertain outlook for peace. The conflict in Yemen began in 2014 and escalated in early 2015 when the Houthi militias and their allied forces occupied large parts of the country and putting in jeopardy the then existing transition process that had been established in late 2011. Yemen has witnessed cycles of violence and civil war since becoming a Republic in 1962. Over the last 50 years, and prior to 1990 also in form of North and South Yemen, Yemen has seen open societal violence, upheaval, and civil wars. Addressing these weaknesses, fragilities, frustrated hopes and rights, recovery of livelihoods, and rebuilding the country physical infrastructure and especially its institutions to end Yemen’s cycles of violence will dominate the political agenda of the country for years to come. These series of policy notes will contribute to this agenda with a focus on the short term, the first two years of recovery in an assumed post conflict situation. There are many conceivable needs and possible entry points for this note series. In interaction with representatives of the recognized Government, other Yemeni actors, and expertise available within the Bank, drawing also on experience in other countries, these notes cover (1) key elements for economic stabilization and public trust building, (2) proposals to bring in private sector capacity for recovery and generation of employment, (3) recommendation for how best to restore services to citizens while focusing also on institutional set-ups that forge inclusiveness, participation, and transparency, taking account for a fragmented central state level, and (4) a critical review and analysis on how the Yemen authorities and Yemen’s foreign partners can best use external support for recovery, reconstruction, and ultimately for development.